Strategic Responses to Quality Management in Turkish Higher Education. - SABIR TAŞTAN, Nalan; TAŞTAN, Kürşat; YILMAZ, Sinan (Journal of Social Sciences Research / Sosyal Bilimler Araştırmaları Dergisi)
In the study, a neo-institutionalist pre-conceptual framework was followed which was developed to identify the different strategic responses that organizations put forth because of institutional pressures towards conformity and to predict the formation of alternative strategies. In this context, it has been tried to determine which strategic responses (acquiesce or defy or manipulate) are given faced with normative pressures to adopt quality management in Turkish higher education from a Neo-Institutionalist perspective. In the study, PLS-SEM algorithms were applied with SmartPLS software. The findings concluded that the "acquiesce" strategic response against normative pressure from the institutional pressures for the adoption of quality management in Turkish higher education, and the "manipulate" strategic response is given against mimetic pressure. According to the results obtained in this study, the acquiesce response as a strategic response to the normative pressures for higher education institutions to adopt quality management reveals that normative pressure is an essential tool for establishing quality in higher education. This indicates that success has been achieved in the systematic establishment of quality management on a national basis in Turkiye. Conformity to Standards and Guidelines for Quality Assurance in the European Higher Education Area (ESG) standards brings success to Turkish higher education and enables Turkiye to complete its integration with Europe in higher education as soon as possible.